Pregnancy outcome in patients with inflammatory bowel disease treated with thiopurines: cohort from the CESAME Study. Issue 2 (29th November 2010) - Coelho, Jessica; Beaugerie, Laurent; Colombel, Jean Frédéric; Hébuterne, Xavier; Lerebours, Eric; Lémann, Marc; Baumer, Philippe; Cosnes, Jacques; Bourreille, Arnaud; Gendre, Jean Pierre; Seksik, Philippe; Blain, Antoine; et al.
Abstract : Background and aims: Few studies have been conducted addressing the safety of thiopurine treatment in pregnant women with inflammatory bowel disease (IBD). The aim of this study was to evaluate the pregnancy outcome of women with IBD who have been exposed to thiopurines. Methods: 215 pregnancies in 204 women were registered and documented in the CESAME cohort between May 2004 and October 2007. Physicians documented the following information from the women: last menstrual date, delivery term, details of pregnancy outcome, prematurity, birth weight and height, congenital abnormalities, medication history during each trimester, smoking history and alcohol ingestion. Data were compared between three groups: women exposed to thiopurines (group A), women receiving a drug other than thiopurines (group B) and women not receiving any medication (group C). Results: Mean age at pregnancy was 28.3 years. 75.7% of the women had Crohn's disease and 21.8% had ulcerative colitis, with a mean disease duration of 6.8 years at inclusion. Of the 215 pregnancies, there were 138 births (142 newborns), and the mean birth weight was 3135 g. There were 86 pregnancies in group A, 84 in group B and 45 in group C. Interrupted pregnancies occurred in 36% of patients enrolled in group A, 33% of patients enrolled in group B, and 40% of patients enrolled in group C; congenital abnormalities arose in 3.6% of group A cases and 7.1% of group B cases. No significant differences were found between the three groups in overall pregnancy outcome. Conclusions: The results obtained from this cohort indicate that thiopurine use during pregnancy is not associated with increased risks, including congenital abnormalities.